Dampak Teknologi IoT terhadap Mobilitas Cerdas dalam Konteks Smart City: Tinjauan Naratif - Rizki Misbah Hidayat (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This research discusses the impact of Internet of Things (IoT) technology on smart mobility in the context of Smart City development. The research also highlights the importance of community involvement in IoT deployment to ensure the successful development of smart mobility. The background of this research focuses on the increasingly complex challenges of mobility in big cities. The research objective is to explore how IoT can improve the efficiency and effectiveness of urban transportation systems. The method used is a narrative review of relevant literature, which includes various case studies and IoT implementations in various cities. The results show that the application of IoT in transportation systems can reduce congestion, improve safety, and facilitate interaction between the government and the public. The conclusion of this study confirms that IoT technology is key to achieving sustainable smart mobility in Smart City development.